The effect of various physical exercise modes on perceived psychological stress - Magalhaes, M (South African Journal of Sports Medicine, 2014)
Background. Stress is an integral part of daily living, but chronic activation of the stress response without the ability to express the physical response results in overloading of the physiological and psychological systems. Objective. To decrease perceived stress by means of one known and/or one relatively unknown physical activity, namely aerobic exercise and somatic awareness exercise. Methods. This investigation made use of a quantitative, comparative, experimental research design over an 8-week period using pre- and post-tests. Participants were measured for psychological stress using a perceived stress scale. The participants were divided into those who were physically untrained and those who participated in exercise training programmes. Results. There were five groups in total. The physically untrained individuals were divided into four groups: a somatic awareness exercise group (n=9); an aerobic exercise group (n=15); a combination group taking part in both somatic awareness and aerobic exercise (n=8); and a control group (n=15). The 5th group contained individuals who participated in physical exercise prior to entering the programme; they were given somatic awareness exercise (n=9) in addition to their existing physical exercises. An independent samples t-test revealed significant changes for perceived stress in the aerobic, somatic, combination and exercise groups, with a 95% confidence level in comparison with the control group. Conclusion. Various physical modes such as aerobic exercise, somatic awareness training and a combination of the two may be used to decrease one’s perceived stress in moderately to highly stressed individuals who are sedentary or who are physically active